Enhanced Energy Harvesting of Flexural Waves in Elastic Beams by Bending Mode of Graded Resonators - De Ponti, Jacopo Maria; Iorio, Luca; Riva, Emanuele; Braghin, Francesco; Corigliano, Alberto; Ardito, Raffaele (Frontiers in Materials, 2021)
We show efficient elastic energy transfer and wave confinement through a graded array of resonators attached to an elastic beam. Experiments demonstrate that flexural resonators of increasing lengths allow to reduce wave scattering and to achieve the rainbow effect with local wavefield amplifications. We show that the definition of a monotonically decreasing distribution of the natural frequencies of the resonators along the wave propagation direction, is the preferable choice to increase the energy efficiency of the system. The proposed configuration is suitable for micro-fabrication, envisaging practical applications for micro-scale vibration energy harvesting.